Mathematical foundations of fuzzy sets - Wu, Hsien-Chung (Chichester, West Sussex, UK Wiley, 2023)
Mathematical Foundation of Fuzzy Sets addresses both GRS and GMSE, although with a much stronger emphasis on the former. For completeness, this book begins with a review of shear strength of soils and classical earth pressure theories. The load-deformation behaviour of GRS mass as a composite, reinforcing mechanisms of GRS, and GRS walls with different types of facing, are then covered, followed by the use of geosynthetics as reinforcement. Design concepts with examples are also fully covered, as is the construction of GRS walls, including construction procedures and general construction guidelines."--
Mathematical Foundations of Fuzzy Sets
Mathematical Analysis
Fuzzy Sets
Set Operations of Fuzzy Sets
Generalized Extension Principle
Generating Fuzzy Sets
Fuzzification of Crisp Functions
Arithmetics of Fuzzy Sets
Inner Product of Fuzzy Vectors
Gradual Elements and Gradual Sets
Duality in Fuzzy Sets
Mathematical Notations
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Fuzzy sets; Electronic books -- Fuzzy mathematics -- Fuzzy sets -- Logic -- MATHEMATICS